Selenium and Mercury Toxicity: The Tale of Fish - Razieh Farzad; Jeanette Andrade (EDIS, 2022)
Not only is fish a good source of protein, but it also provides essential fatty acids such as omega-3, vitamins such as vitamin D, and minerals such as selenium. However, consumers are concerned about exposure to mercury through fish consumption. The degree of exposure to mercury depends on both the amount and the type of fish consumed. Additionally, recent studies have shown that Se can prevent mercury poisoning. To better understand the risk of mercury exposure through seafood consumption, understanding selenium-mercury interaction is useful. This new 4-page document is the first in a "Fish and Human Nutrition" series, which seeks to help consumers make a knowledge-based decision when choosing their seafood. Written by Razieh Farzad and Jeanette Andrade and published by the UF/IFAS Food Science and Human Nutrition Department. https://edis.ifas.ufl.edu/fs437